OBSERVATIONS ON THE SEASONAL PRAWN FISHERY OF THE LITTLE RANN OF KUTCH DURING 1980 - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
The Little Rann of Kutch supports a lucrative seasonal prawn fishery, principally constituted by juveniles of Metapenaeus kutchensis, during the monsoon months. About 2770 fishermen are actively engaged in the fishery, with 307 boats and 1600 nets. The craft and gear operating the fishery are described. An estimated catch of 2311.5 tonnes of prawns was exploited during the 1980 season. Surbari is the biggest of the landing centres with an estimated catch of 688.7 t. Juveniles of 71-95 mm length formed the mainstay of the fishery.